Predictive factors of prostate cancer diagnosis with PSA 4.0–10.0 ng/ml in a multi-ethnic Asian population, Malaysia - Yii, Raymond Shi Liang; Lim, Jasmine; Sothilingam, Selvalingam; Yeoh, Wei Sien; Fadzli, Ahmad Nazran; Ong, Teng Aik; Kuppusamy, Shanggar; Razack, Azad Hassan Abdul (Elsevier, 2020)
Objectives: To identify the associated factors determining prostate cancer detection using transrectal ultrasound (TRUS)-guided prostate biopsy, within a multi-ethnic Malaysian population with prostate specific antigen (PSA) between 4.0 and 10.0 ng/ml. Methods: Study subjects included men with initial PSA between 4.0 and 10.0 ng/ml that have undergone 12-core TRUS-guided prostate biopsy between 2009 and 2016. The prostate cancer detection rate was calculated, while potential factors associated with detection were investigated via univariable and multivariable analysis. Results: A total of 617 men from a multi-ethnic background encompassing Chinese (63.5%), Malay (23.1%) and Indian (13.3%) were studied. The overall cancer detection rate was 14.3% (88/617), which included cancers detected at biopsy 1 (first biopsy), biopsy 2 (second biopsy with previous negative biopsy) and biopsy ≥ 3 (third or more biopsies with prior negative biopsies). Indian men displayed higher detection rate (23.2%) and increased risk of prostate cancer development (OR 1.85, 95% CI 1.03–3.32, p < 0.05), compared to their Malay (9.8%) and Chinese (14.0%) counterparts. Multivariable analysis revealed that ethnicity and PSA density (PSAD) are independent factors associated with overall prostate cancer detection rate. A unit increase of PSAD reflected an increase in PSA after controlling for prostate volume. Conclusion: Prostate cancer detection in Malaysia is comparatively lower. Our study suggests that ethnicity and PSA density should be considered when recommending first or repeat TRUS-guided prostate biopsy for prostate cancer detection in a multi-ethnic Malaysian population. © 2019